2020
DOI: 10.1186/s12875-020-01257-z
|View full text |Cite
|
Sign up to set email alerts
|

Awareness, utilization and influencing factors of social supports for main informal caregivers of schizophrenia patients: a cross-sectional study in primary care settings in Beijing, China

Abstract: Background Most schizophrenia patients are supported by main informal caregivers at home in China. This study aims to investigate the further needs of social supports for main informal caregivers of schizophrenia patients and to analyze influencing factors on the awareness and utilization of social supports in Beijing. The results of this study could potentially act as reference for health professionals to implement appropriate and effective support programs. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“… 7 It is shown that families living with schizophrenia are more vulnerable to discrimination in China. 26 34 Patients with schizophrenia and their caregivers have to cope not only with their symptoms but also with prevalent negative societal attitudes causing stigma, which would isolate a family from mutual help and maintaining quality of life. 38 The psychiatric stigmatisation and discrimination discourage against families living with schizophrenia might lead to increased physical, mental and financial burdens on family members.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“… 7 It is shown that families living with schizophrenia are more vulnerable to discrimination in China. 26 34 Patients with schizophrenia and their caregivers have to cope not only with their symptoms but also with prevalent negative societal attitudes causing stigma, which would isolate a family from mutual help and maintaining quality of life. 38 The psychiatric stigmatisation and discrimination discourage against families living with schizophrenia might lead to increased physical, mental and financial burdens on family members.…”
Section: Discussionmentioning
confidence: 99%
“…This helps to alleviate increased risk of drifting into or remaining in poverty caused by increased health expenditure, reduced productivity, stigma, and loss of employment and associated earnings based on social drift theory 7. It is shown that families living with schizophrenia are more vulnerable to discrimination in China 26 34. Patients with schizophrenia and their caregivers have to cope not only with their symptoms but also with prevalent negative societal attitudes causing stigma, which would isolate a family from mutual help and maintaining quality of life 38.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For the potential increased risk of schizophrenia, more prevention and management measures are needed. The government is suggested to allocate sufficient human and facilities resources, strengthen the ability of the general practitioners to identify high-risk populations, and take early intervention to prevent high-risk individuals from developing schizophrenia ( 39 ). In addition, social support is also important for individuals to manage stressful life events and prevent triggers for schizophrenia.…”
Section: Discussionmentioning
confidence: 99%